The Influence of Leadership Style and Organizational Commitment on Employee Performance of Makassar City Manpower Office - Muhammad Amirul Haq; Manan Sailan; Risma Niswaty (Jurnal Ad'ministrare, 2021)
This research was conducted for the Makassar City Manpower Office. This study aims to determine 1) transformational and transactional leadership styles, 2) employee commitment levels, 3) employee performance levels, 4) the effect of transformational leadership on employee performance, 5) the effect of transactional leadership on employee performance, 6) the effect of transactional leadership on performance. employees. organizational commitment to employee performance. employee performance, 7) The relationship and influence of transformational leadership and organizational commitment to employee performance, 8) Relationship and influence of transactional leadership and organizational commitment to employee performance. The research method used is quantitative research with a population of 120 people and a sample of 70 respondents. The research instrument used questionnaires and documentary methods, while the data analysis technique used descriptive analysis and multiple linear regression. The results of this study indicate that transformational leadership is highly rated based on employee observations, the level of organizational commitment, and employee performance has high scores, even though transactional leadership is rated below average. In conclusion, points four to six have a low positive effect, while points seven and points eight also have a low positive effect and the relationship of the two independent variables has a low value